UJI DAYA TERIMA DAN ANALISIS KANDUNGAN GULA TOTAL PADA SOFTDRINK BUNGA ROSELLA DAN STEVIA SEBAGAI MINUMAN ALTERNATIF UNTUK PENDERITA DIABETES MELLITUS - Tiara Handayani; Khoirun Nisa Alfitri; Diah Puspitasari (JURNAL TEKNOLOGI PANGAN DAN ILMU PERTANIAN (JIPANG), 2025)
Diabetes mellitus is a metabolic disease whose prevalence continues to increase and is associated with high sugar consumption. One of the strategies for managing diabetes is the development of low-calorie functional beverages that remain sensorially acceptable. This study aims to test the acceptability and analyze the total sugar content of soft drinks based on roselle flowers (Hibiscus sabdariffa L.) and stevia (Stevia rebaudiana Bertoni) as a natural zero-calorie sweetener. This research uses an experimental method with a non-factorial Completely Randomized Design (CRD). Four formulations were tested, namely: F0 (2.5% roselle + 16% granulated sugar), F1 (2.5% roselle + 0.5% stevia), F2 (2.5% roselle + 0.7% stevia), and F3 (2.5% roselle + 1% stevia). A hedonic test was conducted on the parameters of color, aroma, taste, and texture by semi-trained panelists with inclusion criteria (students had already received material related to hedonic testing, were willing to be panelists, were physically and mentally healthy, and had eaten more than 30 minutes prior) and exclusion criteria (flu or anosmia, ageusia or loss of taste, a history of stomach acid, and smoking). Data were analyzed using Kruskal-Wallis followed by Post Hoc Mann-Whitney. The results of the hedonic test for taste (p=0.0039) and color (p=0.0035) attributes showed significant differences, while there were no significant differences for aroma (p=0.2796) and texture (p=0.1975) attributes. Post-hoc analysis showed that F1 was preferred over F3. The total sugar content of F1 was 9,74%, while that of F0 was 7,54%. The independent t-test showed a significant difference between the total sugar content of F1 and F0 (p=0.0003).